Outcome Compartison of Concomitant Arthroscopic SLAP / Anterior Bankart Repair with SLAP /Posterior Bankart Repair - Henn, Ralph Frank (Orthop J Sports Med, 2013)
OBJECTIVES: Combined unstable tears of the superior labrum (SLAP) and either the anterior or posterior labrum are not uncommon. The goal of this study was to directly compare the results of combined anterosuperiorlabral repairs to combined posterosuperiorlabral repairs. METHODS: This is a retrospective study of 34 shoulders (34 patients) treated by a single surgeon at a mean follow up of 25 months (range 12 to 67). 18 patients underwent both SLAP and anterior Bankart repair (AS group) and 15 patients underwent both SLAP and posterior Bankart repair (PS group). All patients had glenohumeral instability (humeral head could be translated over the glenoid rim) on examination under anesthesia in the direction of the Bankart tear. Patients were evaluated with the ASES shoulder score, Simple Shoulder Test (SST), and visual analog scale for pain (VAS), subjective shoulder value (SSV), Short Form 12 (SF12), and physical examination. The two groups were compared using chi-square and t-tests. RESULTS: The mean age in the AS group was 33 years compared to 35 in the PS group (p=0.63). Fifteen patients in each group were men, with 3 women in the AS group and 1 in the PS group (p=0.30). Outcomes in both groups were excellent, with no significant differences between the groups with respect to the ASES, VAS, SSV, SST, SF12 or range of motion at follow-up. Three months postoperatively, the AS group had significantly (p=0.005) less average external rotation (52±16 degrees) compared to the PS group (67.3±5 degrees). 3 shoulders had adverse outcomes in the AS group (1 recurrent anterior instability and 2 required arthroscopic capsular releases) compared to 1 shoulder (revision posterior Bankart) in the PS group (p=0.56). CONCLUSION: The results of combined Bankart and SLAP repairs are excellent. Combined tears were more common in men. The outcomes were similar in both AS and PS groups at 2-year follow-up. Stiffness was more common in the AS group with a transient deficit in average external rotation at 3 months and two patients that required capsular release.